Operationsindikationen bei zystischen Tumoren des Pankreas - Brunner, Maximilian; Belyaev, Orlin; Bösch, Florian; Müller-Debus, Charlotte Friederieke; Radulova-Mauersberger, Olga; Wellner, Ulrich Friedrich; Keck, Tobias; Uhl, Waldemar; Werner, Jens; Witzigmann, Helmut; Grützmann, Robert (Zentralblatt für Chirurgie, 2020)
A steady improvement in modern imaging as well as increasing age in society have led to an increasing number of cystic pancreatic tumours being detected. Pancreatic cysts are a clinically challenging entity because they span a broad biological spectrum and their differentiation is often difficult, especially in small tumours. Therefore, they require a differentiated indication for indication of surgery. To determine recommendations for the surgical indication in cystic tumours of the pancreas, a quality committee for pancreatic diseases of the German Society for General and Visceral Surgery performed a systematic literature search and created this review. Based on the current evidence, signs of malignancy and high-risk criteria (icterus due to cystic pancreatic duct obstruction in the bile duct, enhancing mural nodules ≥ 5 mm or solid components in the cyst or pancreatic duct ≥ 10 mm), as well as symptoms, are a surgical indication, independently of the cyst entity (except pseudocysts). If the entity of the pancreatic cyst is detectable by diagnostic imaging, all main duct IPMN and IPMN of the mixed type, all MCN > 4 cm and all SPN should be resected. SCN and branch-duct IPMN without worrisome features do not constitute an indication for surgery. The indication of operation in branch-duct IPMN with relative risk criteria and MCN < 4 cm is the subject of current discussions and should be individualised. By defining indication recommendations, the present work aims to improve the indication quality in cystic pancreatic tumours. However, the surgical indication should always be individualised, taking into account age, comorbidities and the patient's wishes.
CRIS-Team Scopus Importer:2020-09-04